A new thermodynamic index for thunderstorm detection based on cloud base height and equivalent potential temperature. (1st October 2020) - Samanta, Shrayasi; Tyagi, Bhishma; Vissa, Naresh Krishna; Sahu, Rajesh Kumar
Abstract: Cloud base height (CBH), and equivalent potential temperature ( θe ) at 850 hPa are able to distinguish convective events day. The present work is analysing CBH and θe as ingredients for the formulation of a new thermodynamic index over a tropical station Kolkata during pre-monsoon season of 2016–2019. We have performed skill score analysis to evaluate the performance of new index. The result shows that the ratio CBH/ θe work better than CBH or θe alone in differentiating thunderstorms. The index has been validated by taking thunderstorm cases over Kolkata from published literature, outside the index formulating period. Highlights: The study proposes a new thermodynamic Index based on Cloud base height and θe for thunderstorms. The analysis is based on pre-monsoon (March–May) thunderstorms over Kolkata for 2016–2019. The newly proposed index is working better than existing indices. The index has been validated for different thunderstorms cases outside the study period.